Respuestas
Respuesta dada por:
2
a) 3x-2=5x+8
-2x=10
x=-5
b) 7x-3=4x+9
3x=12
x=4
c) 5x-6=6x-2
-x=4
x=-4
d) 9x-5=6x+13
-3x=21
x=-7
e) 10x+2=7x-7
3x=-9
x=-3
f) 8x-3=5x+7
3x=10
x=10/3
g) 9x-2=2x+12
7x=14
x=2
h) 10x-5=5x+15
5x=20
x=4
i) 7x-9=2x+1
5x=10
x=2
j) 9x-3=8x-2
x=1
k) 5x-6=-6x+3
11x=9
x=9/11
-2x=10
x=-5
b) 7x-3=4x+9
3x=12
x=4
c) 5x-6=6x-2
-x=4
x=-4
d) 9x-5=6x+13
-3x=21
x=-7
e) 10x+2=7x-7
3x=-9
x=-3
f) 8x-3=5x+7
3x=10
x=10/3
g) 9x-2=2x+12
7x=14
x=2
h) 10x-5=5x+15
5x=20
x=4
i) 7x-9=2x+1
5x=10
x=2
j) 9x-3=8x-2
x=1
k) 5x-6=-6x+3
11x=9
x=9/11
Preguntas similares
hace 6 años
hace 9 años
hace 9 años